Toxicology studies of primycin-sulphate using a three-dimensional (3D) in vitro human liver aggregate model. (5th November 2017) - Pénzes, Ágota; Mahmud Abdelwahab, Elhusseiny Mohamed; Rapp, Judit; Péteri, Zsanett A.; Bovári-Biri, Judit; Fekete, Csaba; Miskei, György; Kvell, Krisztián; Pongrácz, Judit E.
Highlights: Primycin is an antibiotic with broad antimicrobial spectrum. Primycin-sulphate at 1 μg/ml and below did not show cytotoxicity in human liver aggregate models. Primycin-sulphate at 1 μg/ml concentration affected gene expression up-regulating 184 and down-regulating 259 genes. Primycin-sulphate at 1 μg/ml de-regulated lipid metabolism. Abstract: Primycin-sulphate is a highly effective compound against Gram (G) positive bacteria. It has a potentially synergistic effect with vancomycin and statins which makes primycin-sulphate a potentially very effective preparation. Primycin-sulphate is currently used exclusively in topical preparations. In vitro animal hepatocyte and neuromuscular junction studies (in mice, rats, snakes, frogs) as well as in in vitro human red blood cell experiments were used to test toxicity. During these studies, the use of primycin-sulphate resulted in reduced cellular membrane integrity and modified ion channel activity. Additionally, parenteral administration of primycin-sulphate to mice, dogs, cats, rabbits and guinea pigs indicated high level of acute toxicity. The objective of this study was to reveal the cytotoxic and gene expression modifying effects of primycin-sulphate in a human system using an in vitro, three dimensional (3D) human hepatic model system. Within the 3D model, primycin-sulphate presented no acute cytotoxicity at concentrations 1 μg/ml and below. However, even at low concentrations, primycin-sulphate affected gene expressions by up-regulating inflammatory cytokines ( e.g., IL6), chemokines ( e.g., CXCL5) and by down-regulating molecules of the lipid metabolism ( e.g., peroxisome proliferator receptor (PPAR) alpha, gamma, etc). Down-regulation of PPAR alpha cannot just disrupt lipid production but can also affect cytochrome P450 metabolic enzyme (CYP) 3A4 expression, highlighting the need for extensive drug–drug interaction (DDI) studies before human oral or parenteral preparations can be developed.